1981
DOI: 10.1139/m81-129
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Campylobacter jejuni in fresh eviscerated whole market chickens

Abstract: A total of 100 fresh eviscerated whole market chickens, purchased one per week over a 5-week period from each of 20 different food stores in the Ontario and Ohio regions, were examined for the presence of Campylobacter jejuni. The microorganism was recovered from 62 and 54% of the chickens in Ontario and Ohio, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 6 publications
3
48
0
Order By: Relevance
“…In general, the occurrence of human campylobacter gastroenteritis has been largely attributed to the consumption of contaminated food animal products, especially poultry, because of the high prevalence of campylobacters in these animals (3,10,12,27,43). A growing body of evidence, however, suggests that other vehicles such as red meat, environmental water, and unpasteurized milk may be important sources of these organisms (19,25,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the occurrence of human campylobacter gastroenteritis has been largely attributed to the consumption of contaminated food animal products, especially poultry, because of the high prevalence of campylobacters in these animals (3,10,12,27,43). A growing body of evidence, however, suggests that other vehicles such as red meat, environmental water, and unpasteurized milk may be important sources of these organisms (19,25,44).…”
Section: Discussionmentioning
confidence: 99%
“…Casecontrol studies have identified a significant association between Campylobacter infection in humans and handling and consumption of poultry (3,10,12,27,43). However, other studies have reported an association with cattle (2, 8, 19, 28-30, 41, 53, 54, 59, 61).…”
mentioning
confidence: 99%
“…Campylobacterjejuni contamination of commercially produced chickens has been widely reported (Smith & Muldoon, 1974;Simmons & Gibbs, 1979;Park et al 1981;Shanker et al 1982). Serotyping of human C. jejuni isolates has shown that many chicken and human strains are of the same serotype (Lior et al 1981;McMyne et al 1982;Munroe, Prescott & Penner, 1983;Abbott et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Handling and consumption of poultry or poultry-related products are considered to be a primary source for Campylobacter-induced disease in humans (5,18,24). Campylobacter has been cultured from as many as 75% of the live broiler population and from as much as 80% of processed poultry meat samples sold commercially (13,14,19,27).…”
mentioning
confidence: 99%